Slim Modiolar Electrode Placement in Candidates for Electroacoustic Stimulation. Issue 3 (8th December 2022) - Kay-Rivest, Emily; Winchester, Arianna; McMenomey, Sean O.; Jethanamest, Daniel; Roland, J. Thomas; Friedmann, David R.
Abstract : Objectives: To determine rates of hearing preservation and performance in patients who met candidacy for electroacoustic stimulation (EAS) and were implanted with a slim modiolar electrode (CI532 or CI632). Design: Adult patients meeting Food and Drug Administration criteria for electroacoustic stimulation (preoperative low-frequency pure-tone average [LFPTA] less than 60 dB at 125, 250, and 500 Hz and monosyllabic word scores between 10% and 60% in the ear to be implanted), who received a slim modiolar electrode were included. Main outcome measures included rates of hearing preservation, defined as a LFPTA ≤80 dB at 125, 250, and 500 Hz, as well as postoperative low-frequency pure-tone threshold shifts, consonant-Nucleus-Consonant (CNC) word scores and AzBio sentences in noise scores. Results: Forty-six patients met inclusion criteria during a 4-year period. Mean (standard deviation) preoperative LFPTA was 34.5 (13.0) dB, and 71.7% had preserved hearing at initial activation. The mean LFPTA shift in patients who preserved hearing at initial activation was 19.7 (14.6) dB, compared with 62.6 (17.7) dB in patients who did not preserve hearing as per our definition. Perioperative steroid use was not different in patients with and without preserved hearing (X 2 (1, N = 46) = 0.19, p = .67, V = 0.06). One year after surgery, 57% of patients had a decline in LFPTA >80 dB and were no longer considered candidates for EAS, with 34.7% still retaining low-frequency thresholds ≤80 dB. CNC word scores at 1 year were 69.9% and 61.4% among individuals with and without preserved low-frequency hearing respectively, measured in their CI ear alone, in their regular listening condition of EAS or electric only ( t (32) = 1.13, p = 0.27, d = 0.39, 95% CI = –6.51, 22.86). Device use time did not differ between groups. Among adults with preserved residual hearing at 1 year (n = 16), 44% used EAS, although there was no significant difference in performance between EAS users and nonusers with preserved hearing. Loss of residual hearing over time did not result in a decline in speech perception performance. Conclusion: The present study demonstrated favorable early rates of hearing preservation with a slim modiolar array. Performance was not significantly different in individuals with and without preserved low-frequency acoustic hearing, independent of EAS use. Compared with reports of short electrode use, the loss of residual hearing in patients implanted with this array did not impact speech perception performance.